The Importance of Using Maternal and Child Health Books to Monitor Children’s Growth and Development: A Health Education Program - Tanjung, Ika Citra Dewi; Pratita, Winra; Martineta, Meriza (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Childhood is a continuous process of growth and development. Every parent hopes that their child will grow and develop optimally. To meet these expectations, regular growth and development monitoring are required. In support of this, the Indonesian Ministry of Health provides expectant mothers with the Maternal and Child Health (MCH) book, containing comprehensive guidance on maternal and child health. The present health education program aimed to assess the adequacy of MCH book and its practical application. Health workers (n=50) and mothers (n=50) received guidance on using the MCH book and the importance of taking anthropometric measurements to monitor growth in early childhood. Forty-one mother and toddler pairs participated in the MCH book assessment using a validated and reliable questionnaire. Also, they participated in child health consultations and growth monitoring via anthropometric measurements. Categorical data were expressed as proportions, while factors associated with the completeness of the MCH book were analyzed using the chi-square test. Ten toddlers did not have an MCH book, while 18 (58.1%) had a book with a low level of completion. No statistically significant factors influencing the completeness of MCH books were identified. Within the MCH books, growth and immunization charts were most likely to be completed. During the program, we explained that mothers are encouraged to read the MCH book and can enter measurements themselves so that their children’s growth and development are well documented. After the education and assessment sessions, mothers and health workers were aware of which pages of the MCH book should be completed when toddlers are brought to health facilities, whether healthy or symptomatic. This health education program benefited health workers and mothers as it improved their knowledge and ability to use and complete MCH books for monitoring children’s growth and development.